Instrumentation and Data-Processing Workflow for AMD Neutralization: Linking Rock Formation, Water-Quality Measurements, and Index Computation - Yazid Fanani; Eko Teguh Paripurno; Tedy Agung Cahyadi; Ahmad Mushoffa; Andris Emanuel Korompis; Muhammad Rizky Redy Asmara; Dwi Fitri Yudwiantoro (Department of Physics, Sebelas Maret University, 2025)
We use the Integrated Geo-Hydrochemical Risk Assessment (IGHRA) as a workflow driven by instruments. This workflow connects (i) evidence from rock formations, (ii) repeated water-quality measurements, and (iii) calculations of indices to manage AMD neutralization. The evidence from formations, including sulfide-bearing, quartz/glass-rich, and widely sericitized units, shows why we need CaO to quickly restore pH and precipitate Fe and Mn. Meanwhile, sulfate (SO₄) remains stable and controls overall compliance. We conduct 5 bench tests per condition to assess a series of CaO doses (1–10 g L⁻¹) and a fixed-mass series of CaCO₃ sizes. With CaO, pH increases to about 6.0-6.4 at 10 g L⁻¹. Fe levels drop to about 7-11 mg L⁻¹, Mn to about 0.16 mg L⁻¹, and SO₄ to about 1.7-1.75 g L⁻¹. These changes help quantify the improvements during treatment and reveal the ongoing sulfate load. Indices calculated from post-treatment samples indicate that the PLI(dose) for Fe, Mn, and SO₄ decreases from about 3.2 at 1 g L⁻¹ to about 0.49 at 10 g L⁻¹. At the same time, Residual Risk (RR) falls from about 67% to about 17%. In contrast, the responses from CaCO₃ remain limited by kinetics at low pH, with high indices across different mesh sizes. To turn this chemistry into practical actions, we determine the size of the polishing step using HRT. Existing ponds (about 884 m³) with a flow rate of approximately 0.0256 m³ s-1 provide about 9.6 hours, which is below the target of about 84 hours. A redesigned cell about 10,125 m³ offers around 110 hours for handling solids and buffering performance. Overall, IGHRA transforms treatment-stage measurements into reproducible indices and clear residence-time goals for mine waters close to the surface.